Simbolisme Bromance di Media Sosial - Pandu Bagus Pratama; Sumekar Tanjung (Jurnal Mahasiswa Komunikasi Cantrik, 2021)
Abstract:Bromance is the concept of friendly interactions between men who like each other and even love each other, but have limitations in sexual orientation. This study aims to present an analysis of the Bromance representation between Raditya Dika and Pandu Winoto. The data to be analyzed sourced from the video on Raditya Dika's YouTube Channel. This study uses qualitative methods and Roland Barthes' semiotic analysis techniques. The result of this research is that the researcher found three categories of representation of Bromance in the video, namely in terms of dialogue, action, and appearance. Researchers hope that this research can add insight and literacy in the community, especially Indonesia related to Bromance.